2012
DOI: 10.1007/s00253-012-4627-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant secondary metabolite-induced shifts in bacterial community structure and degradative ability in contaminated soil

Abstract: The aim of the study was to investigate how selected natural compounds (naringin, caffeic acid, and limonene) induce shifts in both bacterial community structure and degradative activity in long-term polychlorinated biphenyl (PCB)-contaminated soil and how these changes correlate with changes in chlorobiphenyl degradation capacity. In order to address this issue, we have integrated analytical methods of determining PCB degradation with pyrosequencing of 16S rRNA gene tag-encoded amplicons and DNA-stable isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 53 publications
2
34
2
1
Order By: Relevance
“…The calculated sequence coverage values for bacteria (63-68 %) were lower than those found by others (Sun et al 2014b;Uhlik et al 2013;Zhang et al 2013). The lower coverage values are reiterated in the rarefaction curves, which indicate that deeper sequencing would most likely have identified greater diversity.…”
Section: Bacterial Analysescontrasting
confidence: 46%
See 1 more Smart Citation
“…The calculated sequence coverage values for bacteria (63-68 %) were lower than those found by others (Sun et al 2014b;Uhlik et al 2013;Zhang et al 2013). The lower coverage values are reiterated in the rarefaction curves, which indicate that deeper sequencing would most likely have identified greater diversity.…”
Section: Bacterial Analysescontrasting
confidence: 46%
“…Pyrosequencing techniques are capable of providing a more comprehensive picture of all microbes present in a sample, including low-abundance species (La Duc et al 2012). The technique has been used in numerous studies to investigate bacterial communities in soils (Uhlik et al 2013;Xiong et al 2014;Yang et al 2012;Zhang et al 2013), and recently, a study focusing on bacterial communities using high-throughput sequencing to investigating ARD soils in China was published (Sun et al 2014a). However, to our knowledge, no studies exist in which both the bacterial and fungal communities of soils affected by ARD have been investigated by high-throughput sequencing.…”
mentioning
confidence: 99%
“…In addition, microcosmbased SIP studies also confirmed that Burkholderia spp. dominated the aerobic degradation of PCB in a biofilm community grown directly on PCB droplets (Tillmann et al, 2005) as well as the degradation process occurring in a PCB-contaminated soil amended with caffeic acid (Uhlik et al, 2013). Table 3 F values and R 2 of tri-, tetra-, penta-, hexa-and hepta-chlorinated biphenyls (tri-CBs, tetraCBs, penta-CBs, hexa-CBs and hepta-CBs) in soils B, T and R. The data (bold figures) are the mean ± standard deviation of five technical replicates.…”
Section: Microbial Community Compositionmentioning
confidence: 99%
“…Watanabe and coworkers beautifully exploited the technique to detect and characterize dominant phenol-degrading bacteria in activated sludge (Watanabe et al 1998 ). In a similar technique, single-strand conformational polymorphism (SSCP), the separation of single-stranded Uhlik et al ( 2013 ) DNA is achieved on the polyacrylamide gel and differences in mobility results due to differences in the folded secondary structure. Here no denaturants are used; hence, DNA molecules of equal size fold and hence move differently according to the DNA base sequences (Schiwieger and Tebbe 1998 ).…”
Section: Genetic Fingerprinting Techniquesmentioning
confidence: 99%